Impact of stress on adolescents during puberty (part 1) - L.A. Strashok; L.I. Rak; H.M. Danylenko; A.V. Yeshchenko; V.L. Kashina-Yarmak; E.M. Zavelya; M.Yu. Isakova (Zaslavsky O.Yu., 2023)
The first part of the presented article deals with the actual problem of stress impact of on the body in adolescence. Puberty is characterized by significant anatomical and physiological, neuroendocrine and psychological changes. During the war in Ukraine, there are many significant factors that provoke stresses, which are superimposed on the stress of puberty. Stressors can lead to significant psychological pressure, physical problems and, as a result, an impact on the physical health and well-being of children and adolescents. A significant stress factor is a change of residence and lifestyle. The article presents the data of own research on the study of the impact of military operations in Ukraine on the psycho-emotional state and health of internally displaced school-aged children and adolescents. An increase in the tense psycho-emotional state with an increase in negative emotions among migrant adolescents compared to the pre-war period is shown. The adolescents' optimistic view of the future indicated a certain potential for resilience. Increased sensitivity to stressful events in adolescents is due to the maturation of stress-sensitive parts of the brain and related changes in hormonal reactivity. The course of a stress reaction is coordinated by an interaction of the stress-realizing and stress-limiting systems. The first part of the article details the neuroendocrine changes in the hypothalamus of an adolescent provoked by a combination of stress and puberty. The effects of corticotropin-releasing hormone, gonadotropin-releasing hormone and gonadotropin-inhibitory hormone, dopamine, serotonin, gamma-aminobutyric acid, and others have been described. In adolescence, the adaptive stress reactions are superimposed on the process of adaptation to sexual maturation, physical growth and psychosocial development. The relationship of hormones and neurotransmitters of the hypothalamus with other neuroendocrine factors is presented in the second part of the article.